Catecholamines in the regulation of angiogenesis in cutaneous wound healing. Issue 11 (19th September 2020) - Chakroborty, Debanjan; Goswami, Sandeep; Basu, Sujit; Sarkar, Chandrani
Abstract: Angiogenesis involves the formation of new blood vessels from preexisting ones, and it is an essential step during cutaneous wound healing, which supports cells at the wound site with nutrition and oxygen. Impaired angiogenesis in the wound tissues results in delayed wound closure and healing. Among the regulators of angiogenesis, the role of catecholamines (epinephrine, norepinephrine, and dopamine) is of interest due to their diverse roles in the process of wound healing. While both norepinephrine and epinephrine mostly inhibit the angiogenic process in cutaneous wounds, dopamine, the other member of the catecholamine family, has interesting and contradictory roles in the regulation of angiogenesis in the wound beds, depending on the type of dopamine receptor involved. The stimulation of dopamine D2 receptors negatively regulates the angiogenic process in normal dermal wounds and thereby delays healing, whereas the stimulation of dopamine D1 receptors promotes angiogenesis and expedites healing in diabetic wounds. Importantly, catecholamines also play important roles in other pathological conditions, and specific agonists and antagonists of catecholamines are available for the treatment of some disorders. Therefore, such drugs may be utilized for the management of angiogenesis to promote the healing of dermal wounds. This review provides a broad overview of the angiogenic process during cutaneous wound healing and the regulatory roles played by catecholamines during the process.